The management and leadership of educational marketing research, practice and applications - Oplatka, Izhar; Hemsley-Brown, Jane, 1950- (Emerald, 2012)
The introduction of educational markets into public and higher education in many countries has led to more competitive environments for schools and higher education institutions. This, in turn, has led to an increased priority being given by school leaders to the marketing of their institutions, largely because the survival of many educational institutions is now dependent on their capacity to maintain or increase their 'market share' of students, funding and resources. This book presents the works of leading scholars and researchers in the field of educational marketing who handle issues of student retention; trust; building relationships with parents, curriculum marketing, strategic marketing, and market orientation in the educational arena. Special attention is given by the authors to the promotion of education in respect to school innovation, success, and accountability. The book is intended to enrich the theoretical and practical knowledge of scholars who are interested in understanding the leadership of educational institutions, and of principals, marketers, and administrators who face inter-institutional competition in the context of schooling, tertiary or higher education.- Resumé vydavatel
Includes index.
Keywords: management školy; marketing; školská správa; školy; vysoké školy; school management; school administration; schools; universities and colleges; elektronické knihy; sborníky; electronic books; papers of several authors